(untitled) (UUM Journal of Legal Studies, 2024)
This article discusses the need and the benefits of establishing an international commercial court in Saudi Arabia. Since Saudi Arabia’s legal system has been criticized regarding its openness to international investments, this issue is observed from the perspective of potential investors and business partners interested in doing business in Saudi Arabia. The aim is to determine how setting up a specialized international commercial court will improve the environment for investments and remove legal uncertainties that arise from the lack of such courts. Furthermore, a brief overview of the international rise of commercial courts worldwide will be provided, with comparative examples of the courts in Dubai and Singapore to reveal how those jurisdictions have adapted to the global economy and ensured their positions as regional leaders and investment hubs. The essential procedural rules will be highlighted to provide ideas and directions for Saudi Arabia. Finally, this article will discuss the challenges the Kingdom faces in the race to become the regional investment leader, and then provide some key takeaways. The objective of this article will be to explain how Saudi Arabia will overcome the challenges in establishing an international commercial court that will specialize in the application and interpretation of international commercial regulations, and why the setting up of an international commercial court will have a positive effect on the attraction of foreign investors to do business in the Kingdom. This will be achieved by examining and discussing Dubai and Singapore as comparative legal systems that have already established flexible dispute resolution forums which have been recognized worldwide.